PENERAPAN TEKNOLOGI PRODUKSI DAN TEKNOLOGI DIGITAL BAGI INDUSTRI RUMAH TANGGA KERUPUK MANGGA DI DESA JATISURA KECAMATAN CIKEDUNG KABUPATEN INDRAMAYU - Sitorus, Henry Binsar Hamonangan; Rizal, Reda; Lukmana, Muhammad Arifudin; Zuchriadi P., Achmad; Martana, Budhi (Jurnal Bakti Masyarakat Indonesia, 2023)
Mango farmers in Jatisura Village, Cikedung District, Indramayu Regency face problems, mangoes are abundant during the fruit season so the price is cheap, while when it is not the fruit season, mangoes are dif icult to obtain, apart from that, the Home Industry of processed mango products is still done conventionally, especially in the process of cutting the dough mango crackers so the cut results are not uniform and require a long time. The solution is that the partners built are still very simple, (3) the limited ability of community groups to manage processed mango product businesses, and (4) marketing access is still low and the marketing system is still conventional. The aim of this activity is to overcome the problems faced by business actors in processed mango products. in improving the processing of mangoes into processed food that can be stored and marketed at any time. In the processing of processed mango products which currently exist in Jatisura Village, they face several problems; (1) the processing process currently carried out is still conventional, (2) a business management system that ensures the quantity and quality of mango fruit production into mango crackers through the application of production technology and digital technology which can provide added value for home industries. Increased product processing is carried out by applying production technology, such as the use of cutting machines, slicing machines and other processing equipment, as well as the application of digital technology to increase product promotion and marketing. The results of this activity have a positive impact on home industry players in processed mango products in the production and marketing processes. ABSTRAK Petani mangga di Desa Jatisura, Kecamatan Cikedung, Kabupaten Indramayu menghadapi permasalahan, mangga melimpah pada musim buah sehingga harga murah, sementara saat tidak musim buah, mangga sulit didapat, selain itu Industri Rumah Tangga produk olahan mangga masih dilakukan secara konvensional terutama pada proses pemotongan adonan kerupuk mangga sehingga hasil potongan tidak seragam dan memerlukan waktu yang lama. Solusinya adalah dibangun mitra masih sangat sederhana, (3) terbatasnya kemampuan kelompok masyarakat dalam mengelola usaha produk olahan mangga, dan (4) masih rendahnya akses pemasaran dan sistem pemasaran masih bersifat konvensional Tujuan dari kegiatan ini untuk mengatasi permasalahan yang dihadapi pelaku usaha produk olahan mangga dalam meningkatkan mengolah mangga menjadi makanan olahan yang dapat disimpan dan dipasarkan setiap saat. Pada proses pengolahan produk olahan mangga yang saat ini sudah ada di Desa Jatisura, mereka menghadapi beberapa permasalahan; (1) proses pengolahan yang dilakukan saat ini masih bersifat konvensional, (2) sistem pengelolaan usaha yang kuantitas dan kualitas produksi buah mangga menjadi kerupuk mangga melalui penerapan teknologi produksi dan teknologi digital yang dapat memberikan nilai tambah bagi industri rumah tangga Peningkatan proses pengolahan produk dilakukan dengan penerapan teknologi produksi, seperti penggunaan mesin pemotong, mesin peniris, dan peralatan pengolahan lainnya, serta penerapan teknologi digital untuk peningkatan promosi dan pemasaran produk. Hasil dari kegiatan ini memberikan dampak positif pada pelaku industri rumah tangga produk olahan mangga dalam proses produksi dan pemasaran.